PERAN SATUAN RESERSE NARKOTIKA DALAM MENANGGULANGI PENYALAHGUNAAN NARKOTIKA DI MASYARAKAT WILAYAH HUKUM POLRES MAJALENGKA - Effendy, Ferry Sofyan; Sihabudin, Aan Anwar; Budiawan, Arie (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
Based on data regarding drug abuse, it is certainly a challenging task for the Majalengka Police Narcotics Investigation Unit. The author's observations indicate that with the lack of training and education programs on the impacts of drug use, the lack of understanding of drug rehabilitation is a significant issue. The purpose of this study is to determine the role of the Narcotics Investigation Unit in tackling drug abuse in the community within the Majalengka Police jurisdiction. This research employed a qualitative method. The data used were primary and secondary data through observation, interviews, and documentation. The results of this study indicate that the role of the Narcotics Investigation Unit in tackling drug abuse in the community within the Majalengka Police jurisdiction has not been optimal. Obstacles include the perception that drug users are part of criminalization, a lack of public awareness regarding rehabilitation, information leaks during raids between the National Police and the National Narcotics Agency (BNN), and a lack of professional medical personnel specifically dedicated to rehabilitation. The efforts include building public awareness that drug users are not criminalized but require appropriate rehabilitation. This includes coordinating rapid raids between the National Police and the National Narcotics Agency (BNN), recruiting professional medical personnel, and educating the public about the impacts of drug use in accordance with Law No. 35 of 2009 concerning Narcotics.